Simultaneous determination of guanine and adenine in human saliva with graphite sparked screen-printed electrodes - Papavasileiou, Anastasios V; Trachioti, Maria G; Hrbac, Jan; Prodromidis, Mamas I (Talanta, 2022)
Saliva represents one of the most useful biological samples for non-invasive testing of health status and diseases prognosis and therefore, the development of advanced sensors enabling the determination of biomarkers in unspiked human whole saliva is of immense importance. Herein, we report on the development of a screen-printed graphite sensor modified with carbon nanomaterials generated by spark discharge for the determination of guanine and adenine in unspiked human whole saliva. The designed sensor was developed with a "green", extremely simple, fast (16 s), fully automated "linear mode" sparking process implemented with a 2D positioning device. Carbon nanomaterial-modified surfaces exhibit outstanding electrocatalytic properties enabling the determination of guanine and adenine over the concentration range 5 - 1000 nM and 25 - 1000 nM, while achieving limits of detection (S/N 3) as low as 2 nM and 8 nM, respectively. The sensor was successfully applied to the determination of purine bases in unspiked human whole saliva following a simple assay protocol based on ultrafiltration that effectively alleviates biofouling issues. Recovery was 96-108%.
Keywords: grafit; Electrochemical Techniques; guanin; Adenine; sliny; Saliva analysis; Noninvasive analysis; lidé; Graphite; Guanine and adenine; Spark discharge; Electrodes; Saliva; adenin; elektrochemické techniky; Guanine; elektrody; Screen-printed electrodes; Humans